PENGEMBANGAN PEMBELAJARAN MATEMATIKA DENGAN MODEL ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) BERBASIS LKS PADA POKOK BAHASAN SEGITIGA DAN SEGIEMPAT DI SMP MUHAMMADIYAH KUPANG - Uke Ralmugiz; St. Muthmainnah Yusuf; Maria M. Nailiu (MEGA: Jurnal Pendidikan Matematika, 2021)
This study aims to determine the feasibility of developing LKS-based ARIAS models on the subject of triangles and quadrilateral. This research and development or Research and Development (R & D). The population in this study were all junior high school students of all VII grade studentsof SMP Muhammadiyah Kupang in consisting of 153 students. While the random sampling technique. The results showed teh development of learning and learning with ARIAS-based LKS models on the subject of triangles and quadrilateral meeting the validity criteria and feasible to use, namely syllabus with validation value of 4,34, RPP with validation value of 4,30 and LKS with validation value of 3,39 accumulated from the assesment conducted by the validator, and the evaluation of each prototypeof syllabus, RPP, and LKS with on the average4,01 which was declared very or feasible to use. The results of student responses on the worksheetwith the ARIAS model as a whole got a very good response with the achievement of an average assesment score test with a value of 83,33% witch was declaredeffective.